Membudayakan Pola Hidup Sederhana dan Menyantuni Dhuafa: Integrasi Nilai Al-Qur'an, Hadis, dan Kajian Kontemporer: Membudayakan Pola Hidup Sederhana dan Menyantuni Dhuafa: Integrasi Nilai Al-Qur'an, Hadis, dan Kajian Kontemporer - yulii_02 yuli_02; Soleh Alfauzan; Muhamad Yahya (CV. ITTC INDONESIA, 2026)
This study analyzes the cultivation of a simple lifestyle (hidup sederhana) and caring for the underprivileged (dhuafa) through Qur'anic and Hadith foundations, integrated with contemporary discourse. Employing a qualitative library research design with a content analysis approach, this study examines three main pillars: (1) the principle of simple living in QS. Al-Furqan: 67 linked to the practices of Islamic and national figures; (2) the prohibition of wastefulness (israf) in QS. Al-Isra': 26–30 integrated with zero waste and circular economy frameworks; and (3) the story of Qarun in QS. Al-Qashash: 79–82 analyzed through the lens of social conflict and integrity theory. Hadith sources further reinforce these three dimensions. The findings reveal that Islamic teachings on simplicity and social care are not only normative religious obligations but also carry profound relevance to contemporary global challenges of consumerism, environmental sustainability, and socioeconomic inequality. This study contributes to integrative Islamic education discourse by demonstrating the coherence between classical Qur'anic wisdom and modern social-ethical frameworks. Keywords: Simple Living, Dhuafa, Israf, Zero Waste, Circular Economy, Qarun, Social Integrity